PENGARUH PENGAWASAN PIMPINAN TERHADAP KINERJA PEGAWAI DI DEPARTEMEN STOCKFIT PT PRATAMA ABADI INDUSTRI JX - marghareta retno daru dewi; Alisa Seftian (Mimbar Administrasi Mandiri, 2024)
This study examines the impact of leadership supervision on employee performance in the Stockfit Department of PT Pratama Abadi Industri JX, Sukabumi Regency. The research uses Monitoring Theory (Vx) by Siagian (2017:115) and Performance Theory (Vy) by Hersey, Blanchard, and Jhonson (1996) in Wibowo (2010:102-105). A quantitative method was employed, with 102 respondents sampled from a population of 200 using Disproportionate Stratified Random Sampling. Data was collected through a Likert scale questionnaire and analyzed using Pearson Product Moment correlation analysis, the Coefficient of Determination formula, and simple linear regression equation model, with hypothesis testing via the t-test. Results indicate that Leadership Supervision (X) was rated as Good, with an average score of 4.0 and a descriptive percentage of 80.19%. Employee Performance (Y) was rated as Very Good, with an average score of 4.2 and a descriptive percentage of 83.80%. Statistical analysis showed a strong positive correlation between Leadership Oversight and Employee Performance (r_xy=0.783, t_(hitung=)12.588 > t_(tabel=)1.983). The Coefficient of Determination (KD) of 0.6130 indicates that 61.3% of the variation in Employee Performance can be explained by Leadership Supervision, with the rest determined by other factors. The linear regression equation model is Y ̂4540.0 + 0.837X, suggesting that changes in Leadership Supervision can predict changes in Employee Performance.